To the 60-th Anniversary of Ivan A. Dyatlov - article Editorial (Проблемы особо опасных инфекций, 2019)
The eighteenth of August 2019, marked the 60th anniversary of Ivan Alekseevich Dyatlov, Doctor of Medical Sciences, professor, academician of the Russian Academy of Sciences, Director of the FBSI ”State Scientific Center of Applied Microbiology and Biotechnology”.